Correction to: The in-between object and the value of the unknown: conservation and representation at Auschwitz-Birkenau State Museum (Holocaust and genocide studies, 2025)
This is a correction to: Tahel Rachel Goldsmith, The in-between object and the value of the unknown: conservation and representation at Auschwitz-Birkenau